2010
DOI: 10.1186/1471-2407-10-580
|View full text |Cite
|
Sign up to set email alerts
|

Herbal compound "Songyou Yin" reinforced the ability of interferon-alfa to inhibit the enhanced metastatic potential induced by palliative resection of hepatocellular carcinoma in nude mice

Abstract: BackgroundLiver resection is a widely accepted treatment for hepatocellular carcinoma (HCC). Our previous clinical study showed that the rate of palliative resection was 34.0% (1958-2008, 2754 of 8107). However, the influence of palliative resection on tumor metastasis remains controversial. The present study was conducted to evaluate the effect of palliative resection on residual HCC and to explore interventional approaches.MethodsPalliative resection was done in an orthotopic nude mice model of HCC (MHCC97H)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Some of these effects could include vessel normalization. We have reported that an herbal formula, Songyou Yin, can attenuate HCC metastases [17], and S. miltiorrhiza is one of the five constituents of the formula [18]. Tan IIA exhibits direct vasoactive [19,20] and certain antitumor properties [21].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these effects could include vessel normalization. We have reported that an herbal formula, Songyou Yin, can attenuate HCC metastases [17], and S. miltiorrhiza is one of the five constituents of the formula [18]. Tan IIA exhibits direct vasoactive [19,20] and certain antitumor properties [21].…”
Section: Introductionmentioning
confidence: 99%
“…Our follow-up research suggests that HCC patients treated with palliative hepatectomy suffered from dramatically worsened metastases, suggesting that palliative hepatectomy enhances the metastatic potential of residual HCC. Although surgery is associated with tumor suppression and prolonged survival in a few cases [ 4 ], increasing number of reports indicate that hepatic resection exacerbates tumor growth and triggers tumor metastasis [ 5 – 7 ]. We found that palliative resection enhances the metastatic potential of residual HCC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although surgery is associated with tumor suppression and prolonged survival in a few cases [ 4 ], increasing number of reports indicate that hepatic resection exacerbates tumor growth and triggers tumor metastasis [ 5 – 7 ]. We found that palliative resection enhances the metastatic potential of residual HCC [ 5 ]. The present study sought to explore the underlying molecular mechanism of this metastasis-enhancing effect.…”
Section: Introductionmentioning
confidence: 99%
“…SYD is similar in composition to other prescriptions of Chinese herbal compounds. For example, Songyou Yin has been reported to inhibit tumor growth and prolong survival in nude mice bearing a human hepatocellular carcinoma xenograft with high metastatic potential (16,17), however its composition is unknown. It has been reported that SYD comprises two cruciferous vegetable species with some bioactive constituents that exhibit antitumor properties (4,18).…”
Section: Discussionmentioning
confidence: 99%